(untitled) (INNOVATIVE ECONOMY, 2025)
Lutsyshyn O.O., Kravchuk N.Ya. FINTECH AS AN INDICATOR OF TRANSFORMATIONS OF THE GLOBAL FINANCIAL LANDSCAPE: TRENDS, CHALLENGES AND POTENTIAL OF UKRAINE Purpose. The aim of the article is to identify key trends in financial technology and assess their impact on the stability and adaptability of financial systems, particularly in Ukraine, in the context of global transformations. Methodology of research. The study uses an interdisciplinary approach that combines the tools of economic theory, financial analytics, innovation theory, and cybersecurity. The methodological basis consists of methods of scientific generalization and abstraction, content analysis of scientific and analytical sources, as well as the case method for analysing key FinTech trends. A systematic approach and elements of system modelling were used to identify the relationships between FinTech innovations, regulatory changes, and economic stability. The Ukrainian context was studied using comparative, analytical and descriptive methods, which made it possible to assess the specifics of FinTech development in wartime and determine its potential for post-war recovery and integration into the global financial space. Findings. Financial technologies (FinTech) were studied as a key indicator of transformations in the global financial landscape in the context of the digitalization of the world economy. It is substantiated that the dynamic development of FinTech innovations is changing traditional models of financial intermediation, the architecture of financial markets, and approaches to regulation, while creating new opportunities and risks for the economic development of states. The main global trends in the transformation of the global financial landscape are analysed, in particular the development of the Open Banking concept, the spread of central bank digital currencies (CBDCs), the introduction of artificial intelligence technologies in financial services, the growing role of ESG finance, and the strengthening of cybersecurity requirements. It is shown that FinTech is a systemic factor in increasing financial inclusion, payment infrastructure efficiency, and financial transaction transparency, while at the same time highlighting the problems of regulatory fragmentation, data protection and technological dependence. Particular attention is paid to analysing the Ukrainian context of FinTech development in the conditions of full-scale war and the prospects for post-war recovery. It is determined that Ukraine has formed a unique model of digital financial stability based on a high level of digitalization of public and financial services, the development of cashless payments, the adaptability of financial institutions, and innovative solutions in the field of cyber security. The potential of FinTech as a tool for economic recovery, attracting investment, expanding access to financial services for the population and businesses, and harmonizing financial regulation with European standards is substantiated. Originality. It has been proven that FinTech goes beyond a purely technological phenomenon and is becoming a strategic element of Ukraine’s economic stability, competitiveness, and integration into global financial processes. It has been concluded that the effective realization of FinTech potential requires coordinated action by the state, the financial sector, and international partners in the areas of regulatory development, cybersecurity, innovation support, and human capital development. Practical value. The research has significant practical value, as its results can be used to shape and improve state policy in the field of financial technology development, modernization of the regulatory environment, and enhancement of the financial system’s stability. The results can be used by government authorities and regulators in developing strategies for the digitalization of the financial sector, by financial market participants in implementing innovative FinTech solutions and managing risks, and in the scientific and educational process in training specialists in finance, economics, and digital technologies. Key words: financial technologies, FinTech, global financial landscape, Open Banking, central bank digital currencies (CBDC), artificial intelligence, cybersecurity, ESG finance, digital transformation, financial inclusion, economic stability.